K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a: =-5-7-8-3=-26

b: =-4-2-5-6=-17

c: =-8-11-4-2=-25

d: -9-15-6-3=-30

e: =-12-9-3-8=-32

29 tháng 12 2015

A=(2+3+...+13)-(1+2+...+12)=2+3+...+13-1-2-...-12=(13-1)+(2-2)+(3-3)+...+(12-12)=12

12 tháng 1 2022

12 nha cậu .

15 tháng 3 2017

\(a,\frac{7}{3}x+5=\frac{9}{6}x-7\)

\(\frac{7}{3}x-\frac{9}{6}x=-7-5\)

  \(\left(\frac{7}{3}-\frac{9}{6}\right).x=-12\)

                  \(\frac{5}{6}.x=-12\)

                        \(x=\left(-12\right):\frac{5}{6}\)

                        \(x=-\frac{72}{5}\)

\(b,3x+\frac{6}{4}=5-\frac{7x}{6}\)

\(3x+\frac{7x}{6}=5-\frac{6}{4}\)

\(\left(3+\frac{7}{6}\right).x=\frac{7}{2}\)

\(\frac{25}{6}.x=\frac{7}{2}\)

\(x=\frac{7}{2}:\frac{25}{6}\)

\(x=\frac{21}{25}\)

\(c,\frac{12}{5}x+6=\frac{17}{3}x+12\)

\(\frac{12}{5}x-\frac{17}{3}x=12-6\)

            \(-\frac{49}{15}x=6\)

                       \(x=6:\left(-\frac{49}{15}\right)\)

                       \(x=-\frac{90}{49}\)

\(d,6\left(3x+7\right)=12\left(2x-4\right)\)

       \(18x+42=24x-48\)

     \(18x-24x=-48-42\)

                 \(-6x=-90\)

                        \(x=15\)

\(e,13\left(2x-9\right)=8\left(3x-13\right)\)

      \(26x-117=24x-104\)

      \(26x-24x=-104+117\)

                      \(2x=13\)

                        \(x=\frac{13}{2}\)

            

26 tháng 4 2018

coi lại câu a

1.1+1.1+1.1+1.1+1.1/1.1+1.1+9.3+6.8+.2

3 tháng 12 2019

\(a.=5-3+12-4-16\)

\(=-2\)
\(b.=-6-\left(-12\right)+7-10\)

\(=6+7-10\)

\(=3\)

a: \(=\dfrac{15}{4}:\dfrac{2-7}{16}-\dfrac{5}{9}\cdot\left(\dfrac{3}{5}+\dfrac{4}{5}\right)\)

\(=\dfrac{15}{4}\cdot\dfrac{16}{-5}-\dfrac{5}{9}\cdot\dfrac{7}{5}\)

\(=\dfrac{-240}{20}-\dfrac{7}{9}=-12-\dfrac{7}{9}=\dfrac{-115}{9}\)

c: \(=\dfrac{1}{5}-\dfrac{7}{2}-\dfrac{3}{2}+\dfrac{5}{4}\)

\(=\dfrac{4+25}{20}-5=\dfrac{29}{20}-\dfrac{100}{20}=\dfrac{-71}{20}\)

d: \(=\dfrac{12}{17}\left(1-\dfrac{1}{15}-\dfrac{4}{5}+1\right)=\dfrac{12}{17}\cdot\dfrac{17}{15}=\dfrac{12}{15}=\dfrac{4}{5}\)

e: \(=\dfrac{2}{15}\cdot\dfrac{9}{8}-\dfrac{7}{4}\cdot\dfrac{9}{8}+\dfrac{25}{36}\)

\(=\dfrac{9}{8}\left(\dfrac{2}{15}-\dfrac{7}{4}\right)+\dfrac{25}{36}\)

\(=\dfrac{9}{8}\cdot\dfrac{8-105}{60}+\dfrac{25}{36}\)

\(=\dfrac{9}{8}\cdot\dfrac{-97}{60}+\dfrac{25}{36}=\dfrac{-1619}{1440}\)

10 tháng 8 2016

2/3-6/12+1/4 = 5/12 

4/12-18/24+5/2 = 25/12

-5/7*11/9+5/7*4/9 = -5/9

-3/8*13/11-3/8*3/11 = -6/11